Measuring Empowerment : Cross Disciplinary Perspectives - Narayan, Deepa (Washington, DC: World Bank, 2012)
Poverty reduction on a large scale depends on empowering those who are most motivated to move out of poverty-poor people themselves. But if empowerment cannot be measured, it will not be taken seriously in development policy making and programming. Building on the "Empowerment and Poverty Reduction Sourcebook," this volume outlines a conceptual framework that can be used to monitor and evaluate programs centered on empowerment approaches. It presents the perspectives of 27 distinguished researchers and practitioners in economics, political science, sociology, psychology, anthropology, and demography, all of whom are grappling in different ways with the challenge of measuring empowerment. The authors draw from their research and experiences at different levels, from households to communities to nations, in various regions of the world. Measuring Empowerment is a resource for all who are interested in approaches to poverty reduction that address issues of inequitable power relations.